Talaromyces marneffei infection and complicate manifestation of respiratory system in HIV-negative children - Yang, Qin; Wu, Yue; Li, Xiaonan; Bao, Yanmin; Wang, Wenjian; Zheng, Yuejie (BMC pulmonary medicine, 2023)
Background Respiratory symptoms are the earliest clinical manifestation of Talaromyces marneffei (TM) infection. In this study, we aimed to improve the early identification of TM infection in human immunodeficiency virus (HIV)-negative children with respiratory symptoms as the first manifestation, analyze the risk factors, and provide evidence for diagnosis and treatment. Methods We retrospectively analyzed six cases of HIV-negative children with respiratory system infection symptoms as the first presentation. Results All subjects (100%) had cough and hepatosplenomegaly, and five subjects (83.3%) had a fever; other symptoms and signs included lymph node enlargement, rash, rales, wheezing, hoarseness, hemoptysis, anemia, and thrush. Additionally, 66.7% of the cases had underlying diseases (three had malnutrition, one had severe combined immune deficiency [SCID]). The most common coinfecting pathogen was Pneumocystis jirovecii , which occurred in two cases (33.3%), followed by one case of Aspergillus sp. (16.6%). Furthermore, the value of β-D-glucan detection (G test) increased in 50% of the cases, while the proportion of NK decreased in six cases (100%). Five children (83.3%) were confirmed to have the pathogenic genetic mutations. Three children (50%) were treated with amphotericin B, voriconazole, and itraconazole, respectively; three children (50%) were treated with voriconazole and itraconazole. All children were tested for itraconazole and voriconazole plasma concentrations throughout antifungal therapy. Two cases (33.3%) relapsed after drug withdrawal within 1 year, and the average duration of antifungal treatment for all children was 17.7 months. Conclusion The first manifestation of TM infection in children is respiratory symptoms, which are nonspecific and easily misdiagnosed. When the effectiveness of anti-infection treatment is poor for recurrent respiratory tract infections, we must consider the condition with an opportunistic pathogen and attempt to identify the pathogen using various samples and detection methods to confirm the diagnosis. It is recommended the course for anti-TM disease be longer than one year for children with immune deficiency. Monitoring the blood concentration of antifungal drugs is important.